Penatalaksanaan Yoga Kehamilan Untuk Mengurangi Nyeri Punggung pada Ibu Hamil Trimester III di Puskesmas Lembang Kec. Lembang Kab. Majene Provinsi Sul-Bar - Nur Fadhilah; Rasmawati Rasmawati (Pusat Riset dan Inovasi Nasional, 2022)
Back pain during pregnancy peaks at week 24 to week 28, when abdominal enlargement reaches its maximum. Pregnancy and childbirth are natural processes that can cause pain. However, many women feel the pain more severely than they should because they are affected by panic and stress. This is known as the fear-tension-pain concept, where fear triggers tension or panic which causes muscles to stiffen and ultimately increases pain. Overcoming this discomfort requires non-conventional therapy, one of which is pregnant gymnastics. Based on this, the community service team conducted the implementation of pregnant exercises for third-trimester pregnant women with the aim that pregnant women can do pregnant exercises independently at home and reduce complaints of back pain they experience. This training method is carried out using lectures and demonstrations of pregnant exercises. Implementation was carried out 1x / once a week for 1 month at Puskesmas Lembang Lego Village, Lembang Kec. Lembang, Polman Regency in January 2021 which 20 pregnant women attended. The care method used is qualitative with case research (CSR) by collecting pre- test and post-test data with pain scale observation using Numeric Rating Scale (NRS) measurement. Physical training of pregnant women to prepare for their labor through pregnancy exercises is considered effective as a preventive measure for pregnant women in preparing for their labor. It can reduce the intensity of back pain in Trimester III pregnancy.